‘‘A STUDY TO EVALUATE THE EFFECTIVENESS OF WARM COMPRESS WITH EPSOM SALT IN REDUCING JOINT PAIN AMONG ELDERLY AT SELECTED COMMUNITY AREAS, HYDERABAD, TELANGANA’’. - Priya Patra; Lisa Leo; Y. Pragna; R. Leelavathy (IJRDO Journal of Tourism and Hospitality, 2025)
A Quasi - experimental study was undertaken to ‘‘Evaluate the effectiveness of warm compress with Epsom salt in reducing joint pain among elderly at selected community areas, Hyderabad, Telangana’’. In this study a quantitative approach and non randomized control group design was adopted. 60 elderly persons with joint pain were selected using non probability convenient sampling technique at Turkayamjal, Hyderabad, Telangana. Numerical pain rating scale was used to assess the level of pain among elderly people. The results of the study revealed that in pre-test in the experimental group 3.3% of the elderly people are having mild pain,13.3% of the elderly people are having moderate pain, 60% of the elderly people are having severe pain and 23.3% of the elderly people are having worst pain where as in the post test 53.3% of the elderly people are having no pain, 26.7% are having mild pain and 20.0% of the elderly people are having moderate pain. In the control group, pre test shows that 23.3% of the elderly people are having moderate pain, 60 % of the elderly people are having severe pain, 16.6 % of the elderly people are having worst pain. In the post test 3.3% of the elderly people are having no pain, 3.3% of the elderly people are having mild pain, 26.6% of the elderly people are having severe pain and 66.6% of the elderly people are having worst pain. The post test mean scores were increased from 2.9 to 3.5, The calculated ‘‘t’’ value was 3.0. The table value was lower than calculated ‘‘ t’’ value. The findings in the experimental group reveals that in post-test pain scores were decreased from 3.03 to 0.66 After administration of warm compress with Epsom salt the calculated ‘‘t’’ value was 21.0 which was greater than calculated ‘‘t’’ value. There was a significant difference between the level of pain scores of elderly people with joint pain before and after the application of warm compress with Epsom salt . Hence Hypothesis [H1] was accepted.